Energy-efficient operation of transcritical and subcritical CO2 inverse cycles via Extremum Seeking Control. (September 2019) - Rampazzo, Mirco; Cervato, Andrea; Corazzol, Chiara; Mattiello, Luca; Beghi, Alessandro; Cecchinato, Luca; Virzi, Andrea
Highlights: This paper considers the control of CO2 transcritical and subcritical systems. A model-free real-time optimization approach (i.e. Extremum Seeking Control) is used. Thanks to the availability of a test rig, two case studies are investigated: a refrigeration system and a heat pump unit. The performances of the ESC have been compared with those provided by the Liao's correlation, which is well-known in the literature. Abstract: In this paper, the energy-efficient operation of single-stage refrigerating carbon dioxide vapour compressor units operating in transcritical and subcritical conditions is discussed from an experimental point of view. The performance of this kind of systems strongly depends on the operating conditions and in particular on the vapour compression cycle (VCC) high pressure. Because of the limited knowledge of certain system parameters and the difficulty of developing and implementing effective model-based control strategies, the problem of determining the optimal value for the VCC high pressure that leads to the maximum system performance is here faced by means of a model-free approach. More specifically, an Extremum Seeking Control (ESC) scheme, which can search for the unknown or slowly varying optimum input with respect to a certain performance index, is adopted. In particular, thanks to the availability of an unusual test rig, different CO2 system configurations, i.e. a refrigeration system and a heat pump unit, have been tested. In this scenario, the performances of the ESC have been compared with those provided by the Liao's correlation, which is well-known in the literature.